2009
DOI: 10.1029/2009ja014057
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the 10 November 2004 storm‐time middle‐latitude plasma bubble event in Southeast Asia using multi‐instrument observations

Abstract: The development and dynamics of ionospheric plasma bubble (PB) irregularity during the super storm of 7–11 November 2004 are investigated using the data from a multi‐instrument network operated in Southeast Asia. Analysis of fluctuations in Global Positioning System total electron content (GPS TEC), ionosonde, GPS scintillation, and in situ satellite density data indicates a series of intense PB‐associated irregularities at equatorial, low, and middle latitudes in the Japanese longitude on 10 November. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 84 publications
1
53
0
Order By: Relevance
“…Therefore, studies related to ESF generation or suppression during an intense geomagnetically disturbed period are assuming great importance. Li et al (2009) have investigated the characteristic of plasma bubbles occurrence in Southeast Asia during the super storm of 7-11 November 2004 using data from GPS, ionosondes, magnetometers and satellite. Li et al (2009) observed that prompt penetration of magnetospheric electric field to equatorial ionosphere contribute to spread-F generation in equatorial and low latitude on 10 November in the Japanese and eastern longitudes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, studies related to ESF generation or suppression during an intense geomagnetically disturbed period are assuming great importance. Li et al (2009) have investigated the characteristic of plasma bubbles occurrence in Southeast Asia during the super storm of 7-11 November 2004 using data from GPS, ionosondes, magnetometers and satellite. Li et al (2009) observed that prompt penetration of magnetospheric electric field to equatorial ionosphere contribute to spread-F generation in equatorial and low latitude on 10 November in the Japanese and eastern longitudes.…”
Section: Resultsmentioning
confidence: 99%
“…Li et al (2009) have investigated the characteristic of plasma bubbles occurrence in Southeast Asia during the super storm of 7-11 November 2004 using data from GPS, ionosondes, magnetometers and satellite. Li et al (2009) observed that prompt penetration of magnetospheric electric field to equatorial ionosphere contribute to spread-F generation in equatorial and low latitude on 10 November in the Japanese and eastern longitudes. Lei et al (2008a,b) have investigated the thermospheric and ionospheric response to this geomagnetic storm using ionospheric observations and Coupled Magnetosphere Ionosphere Thermosphere (CMIT) 2.0 model simulation.…”
Section: Resultsmentioning
confidence: 99%
“…Under geomagnetically disturbed conditions, the density depletions could also be formed at mid-latitudes by penetrating electric field or disturbance electric field just as they are formed in the equatorial region (Li et al, 2009). However, under geomagnetically quiet conditions, radar observations indicate that the mid-latitude F region irregularity structures are quite different from equatorial ones and might be associated with the mid-latitude instabilities .…”
Section: Y Zhang Et Al: Gps Ionospheric Scintillations and Ionogrammentioning
confidence: 99%
“…In recent years, the penetration electric field has been used extensively to interpret various disturbances in the midlatitude and low-latitude ionosphere [e.g., Kelley et al, 2003;Huang et al, 2005;Zhao et al, 2005Zhao et al, , 2008Wei et al, 2008a;Li et al, 2009Li et al, , 2010Guo et al, 2010;Huang, 2009;Zong et al, 2010]. The duskward penetration electric field sometimes can be completely canceled by the dawnward shielding electric field in the ring current, which is called "perfect shielding" [Goldstein, 2006] or "goodshielding" [Wolf et al, 2007].…”
Section: Introductionmentioning
confidence: 99%